Navigating the Pandemic: Social-Legal Approaches for Establishing a Specialized Infectious Disease Hospital - Situmeang, Ampuan; Shahrullah, Rina Shahriyani; Aprisanti, Aprisanti; Ong’eta, Wyclife (Nurani Hukum, 2024)
In accordance with Government Regulation "Perpres No. 52 of 2020," the construction of a Special Infection Hospital (Rumah Sakit Khusus Infeksi/RSKI) was completed, and the BMN administration was transferred to the Ministry of Defense. Currently, the RSKI functions as an emergency clinic dedicated to treating COVID-19 patients explicitly. Once the pandemic is declared over, the RSKI will serve as a medical clinic for maintenance purposes. This study aims to examine and analyze the establishment of the RSKI from legal perspectives. It also to identify challenges or obstacles encountered by the Batam City Government pursuant to the construction of the RSKI for the purpose of treating and reducing the Covid-19 patients. Hence, this study utilized socio-legal research by collecting primary data through in-depth interviews with stakeholders, The secondary data was also used and collected through library research. Both data were analyzed by using qualitative approaches. It was found that the establishment of the RSKI was based on Law Number 44 of 2009 on Hospital. However, the Batam City Government remained to face challenges in handling the Covid-19 pandemic because of a lack of people’s awareness on health protocols, consequently many of them rejected the Covid-19 vaccines. Furthermore, Batam City was pointed as the entry point of the repatriation of Indonesian migrant workers from Malaysia and Singapore. The RSKI had fewer adequate facilities to provide effective treatments to the Covid-19 patients.